"Attempting to say something without saying it …": writing haiku in health care education. Issue 1 (1st June 2003) - Biley, F C; Champney-Smith, J
Abstract : Over a number of years the authors have been running short haiku writing workshops and have been using haiku as an evaluation tool. This paper describes those experiences and uses the haiku generated in these workshops to illustrate how this poetic form can be used as—for example, part of the process of reflection, to explore emotional and practical issues related to clinical health care practice, to refine writing skills and precision and, it is hoped, to convey to others the essence of the experience of health care provision, education and, perhaps, health, illness, and disease.